Relationship between clinical evaluation and ultrasound assessment of rheumatoid arthritis patients using a 12 joint score. (9th February 2017) - Cerqueira, Marcos; Teixeira, Filipa; Sousa Neves, Joana; Peixoto, Daniela; Afonso, Maria Carmo; Costa, José A.
Abstract: Aim: To identify if the use of a systematic ultrasound (US) evaluation has relevance in the determination of disease activity in rheumatoid arthritis patients on biological disease‐modifying anti‐rheumatic drug treatment. Methods: A 12 joint US assessment was performed on the same day of the routine clinical examination. Both Grey‐scale (GS) and Power Doppler (PD) were graded semi‐quantitatively (0–3 scale). Results: Forty‐one patients were included. GS or PD > 0 were found in 24% and 3% of the ankles, 21% and 17% of the wrists, 19% and 9% of the second metacarpophalangeal joints (MCP), 7% and 2% of the third MCP, 6% and 0% of the knees and 5% and 0% of the elbows, respectively; tenosynovitis of the tibialis posterior was found in 19% of the ankles. Eight of the patients with Disease Activity Score of 28 joints (DAS28)≤ 2.6 ( n = 15) had an US score of 0. Twenty‐seven joints (6.7%) had US evidence of synovitis but were not considered to be swollen; 10 (2.5%) were considered to be swollen but had no US evidence of synovitis. Conclusions: Using a 12 joint US assessment, a high proportion of patients with DAS28 < 2.6 were found to have inflammatory US activity, and a significant proportion of patients had evidence of tenosynovitis of the tibialis posterior, which may be difficult to clinically detect. A regular and standardized US assessment of RA patients is therefore warranted to complement clinical evaluation and better define disease activity.